Oral flurbiprofen spray for mucosal graft harvesting at the palatal area: A randomized placebo‐controlled study. Issue 10 (29th August 2018) - Isler, Sila Cagri; Eraydin, Nihal; Akkale, Habibe; Ozdemir, Burcu
Abstract: Background: Flurbiprofen which is a non‐steroidal anti‐inflammatory drug (NSAID), has been safely used for the control of postoperative patient's morbidity after periodontal plastic surgeries requiring palatal graft harvesting, but there is little information on the efficacy of topical use. The aim of the study was to evaluate whether patient pain perception was reduced and patient morbidity was improved by using oral spray of flurbiprofen after palatal graft harvesting. Methods: Forty‐eight patients (21 males and 27 females), scheduled for subepithelial connective tissue graft (SCTG) and free gingival graft (FGG) requiring periodontal plastic surgeries were selected. The patients were randomly assigned to each group and used oral spray of flurbiprofen or placebo three times a day for a week. The palatal donor area was evaluated at 1, 3, 7, 14, 21, 28, 42, and 56‐day follow‐up after the surgery for postoperative pain, patients' discomfort, complete epithelialization, changes in dietary habits, burning sensation, color match, the amount of systemic analgesic consumption and the presence of delayed bleeding. Wound healing scores were recorded at 14‐day follow up. Results: The prevalance of complete epithelialization was significantly higher in the placebo‐FGG group than flurbiprofen‐FGG group at 21 days postoperatively ( P  < 0.05), while there was no significant alteration for both flurbiprofen‐SCTG and placebo‐SCTG groups at any follow‐up periods. In flurbiprofen‐FGG group, significant improvements were observed for postoperative pain, patients' discomfort and burning sensation at 14 days postoperatively ( P  < 0.05). Conclusion: Oral flurbiprofen spray reduces patient's morbidity, however it might have negative effects on epithelialization of secondary wound healing after FGG operations.